Clinical and molecular characterization of an 18‐month‐old infant with autosomal recessive cutis laxa type 1C due to a novel LTBP4 pathogenic variant, and literature review. Issue 7 (21st May 2019) - Ritelli, Marco; Cammarata‐Scalisi, Francisco; Cinquina, Valeria; Colombi, Marina
Abstract: Background: Cutis laxa (CL) is a group of rare connective tissue disorders mainly characterized by wrinkled, redundant, inelastic, and sagging skin. Besides skin anomalies, in most CL forms multiple organs are involved, leading to severe multisystem disorders involving skeletal, cardiovascular, pulmonary, and central nervous systems. CL might be challenging to diagnose because of its different inheritance patterns, extensive phenotypic variability, and genetic heterogeneity. Herein, we report the clinical and molecular characterization of an 18‐month‐old infant with signs suggestive of recessive cutis laxa type 1C (ARCL1C), although with a relatively mild presentation. Methods: To confirm the clinical suspicion, mutational screening of all the exons and intron‐flanking regions of the latent transforming growth factor‐beta binding protein 4 gene ( LTBP4 ) was performed by Sanger sequencing on an ABI3130XL Genetic Analyzer. Results: Apart from the presence of the dermatological hallmark, the reported patient did not show pulmonary emphysema, which is the most common and discriminative finding of ARCL1C together with gastrointestinal and urinary involvement. Indeed, pulmonary involvement only included episodes of respiratory distress and diaphragmatic eventration; intestinal dilation and tortuosity and hydronephrosis were also present. Molecular analysis disclosed the novel homozygous c.1450del (p.Arg484Glyfs*290) pathogenic variant in exon 12 of LTBP4, thus leading to the diagnosis of ARCL1C. Conclusion: Our findings expand both the knowledge of the clinical phenotype and the allelic repertoire of ARCL1C. The comparison of the patient's features with those of the other patients reported up to now offers future perspectives for clinical research in this field. Abstract : Cutis laxa (CL) is a group of rare connective tissue disorders mainly characterized by wrinkled, redundant, inelastic, and sagging skin; in most CL forms multiple organs are involved, leading to severe multisystem disorders involving skeletal, cardiovascular, pulmonary, and central nervous systems. Herein, we report the clinical and molecular characterization of an 18‐month‐old infant with autosomal recessive cutis laxa type 1C due to a novel LTBP4 pathogenic variant, expanding both the knowledge of the clinical phenotype and the allelic repertoire of ARCL1C. The comparison of the patient's features with those of the other 17 patients reported up to now offers future perspectives for clinical research in this field.